Prevalence of human papillomavirus (HPV)-vaccine types by race/ethnicity and sociodemographic factors in women with high-grade cervical intraepithelial neoplasia (CIN2/3/AIS), Alameda County, California, United States. Issue 1 (3rd January 2020) - Saadeh, Kayla; Park, Ina; Gargano, Julia W.; Whitney, Erin; Querec, Troy D.; Hurley, Leo; Silverberg, Michael
Abstract: We evaluated racial/ethnic differences in prevalence of oncogenic HPV types targeted by the quadrivalent HPV vaccine (16/18) and nonavalent HPV vaccine (31/33/45/52/58) in women diagnosed with CIN2/3/AIS after quadrivalent HPV vaccine introduction (2008–2015). Typing data from 1810 cervical tissue specimen from HPV-IMPACT (Alameda County, California, US), a population-based CIN2/3/AIS surveillance effort, were analyzed. Using log-binomial regression, we calculated adjusted prevalence ratios (aPR) and 95% confidence intervals (CI) comparing type prevalence by race/ethnicity, adjusted for health insurance, age, CIN2/3/AIS grade, and time period, overall and in the "early vaccine era" (2008–2011) and "later vaccine era" (2012–2015). Overall, oncogenic HPV16/18 prevalence was significantly lower among black (43%) and Hispanic (43%) women compared with white (52%) women (aPR (95% CI): 0.80 (0.70, 0.93) and 0.80 (0.70, 0.91), respectively). In 2008-2011, proportion of HPV16/18 detected was significantly lower in black (47%), Hispanic (46%), and Asian (42%) women compared to white (58%) women (aPR (95% CI): 0.80 (0.67, 0.96), 0.75 (0.63, 0.90), and 0.73 (0.58, 0.90), respectively). There were no significant differences in 2012-2015. Between the two eras, HPV16/18 prevalence declined in white (−11%), black (−9%), and Hispanic (−6%) women, and increased in Asian women (12%). Decreasing HPV 16/18 prevalence in CIN2/3/AIS lesions in white, black, and Hispanic women may suggest benefit from quadrivalent vaccination. In our unadjusted analysis of HPV31/33/45/52/58, prevalence did not differ significantly by race/ethnicity, but was significantly higher among Hispanic women (32%) compared to white women (27%) after adjustment (aPR (95%CI): 1.22 (1.02, 1.47). Prevalence was also non-significantly higher among black (32%) and Asian (33%) women. This analysis suggests that the nonavalent vaccine's potential for impact against cervical precancers will not be lower in women of color compared to white women. These data underscore the importance of equitable vaccination in facilitating continued declines of vaccine-preventable HPV types among all women.